HUMUS IMPROVEMENT OF TRACE ELEMENTS ADDED LOMBRIZ - Lengua C., Rosa (2003)
Enter the earthworm humus nutrient containing trace elements, in order to improve their quality and thus apply it to farmland. Trace elements are extracted from salts and minerals such as chalcopyrite, pyrolusite, hematite, sphalerite.